Rozie Times: first UiTM living lab @ Kundasang / Galeri Seni Tuanku Nur Zahirah - Universiti Teknologi MARA, Galeri Seni Tuanku Nur Zahirah (GESTURZ) (Galeri Seni Tuanku Nur Zahirah, UiTM, 2022)
Rozie TImes II picks up where the first volume left off, documenting some of the more significant occasions that have taken place since then, right up to the VC's 200th day in office. From her postings we learn of new endeavours, advantageous partnerships, impactful appointments, social enterprises, charity and empathy, among others, all glimpse through her candid reporting. Once again her love and pride for Keluarga UiTM were evidenced, as she jotted down the names and personally thanked individuals from various faculties, departments, centres, offices, organisations, and communities that have made an impression. Rozie Times shares the essence of the Vice-Chancellor's distinctive leadership and viewpoints.